Modal Intelektual dan Dampaknya bagi Keberhasilan Organisasi - T. Elisabeth Cintya Santosa; Rony Setiawan (Jurnal Manajemen Maranatha, 2007)
Business world and economics have been knocked over by a waving drastic change. With new era appearance, information era, hence happened friction " first number position" in economics, what is initialy occupied by physical assets become to be shifted by nonphysical assets, that is asset of intangible. Asset of Intangible, especially in the form of intellectual capital represent answer of appearance waving new world. As a result, intellectual capital become one of the key factor determining efficacy of company. But, the mentioned at the same time represent challenge to company. Intellectual capital have to be processed as optimal as and as maximum so that can give impact and contribution which are positive to company itself in the effort so that company itself stand at bay emulation era which progressively tighten.